The Effectiveness of Healing Interventions for Post-Abortion Grief: A Systematic Review and Meta-Analysis - Leila BAGHERI; Ali Mohammad NAZARI; Reza CHAMAN; Ashraf GHIASI; Zahra MOTAGHI (Tehran University of Medical Sciences, 2020)
Background: Abortion is the ending of pregnancy due to removing an embryo or fetus before it can survive outside the uterus. Some women suffer from psychological disorders such as anxiety, depression and grief after abortion. Early detection of high-risk women after abortion and psychological intervention is one of the healing methods than can lead to improving outcomes but its effectiveness is not clear. The present meta-analysis evaluated the efficacy of this approach. Methods: The international and national electronic databases were searched from Jan 1998 until Aug 2018 including Medline, Web of Knowledge, Ovid, Embase, PubMed, Scopus, Cochrane, ScienceDirect, PsycINFO, ProQuest, Google Scholar, Iranmedex, Scientific Information Database (SID), and Magiran. The pooled mean difference with the random-effects model was used for meta-analyses. The preferred reporting items for systematic reviews and meta-analyses guidelines adhered in this study. Results: We enrolled 7 relevant studies involving 918 subjects into the meta-analysis process. The meta-analysis of the interventions aiming at prevention of post-abortion grief yielded a pooled standardized mean difference (SMD) of −0.03 (95% CI: −0.40−0.34; Z=0.16; P=0.87) at post-test and of -0.21 (95% CI:-0.53-0.10; Z=1.32; P=0.19) at follow-up. Conclusion: This systematic review found psychotherapy-based interventions are effective in post-abortion grief treatment but; we found psychotherapy-based interventions are somewhat effective in short-term post-abortion grief and it has a better effect on long-term grief.